Pregnant women with epilepsy: incidence, management and outcomes. (16th November 2010) - Joy, R; Dick, A; Love, C
Abstract : Introduction: Epilepsy is the second most common neurological disorder encountered in obstetrics after migraine.1 The 7th CEMACH report identifies epilepsy as one of the three pre-existing serious medical health problems that need better access to preconception and antenatal care.2 Objective: To assess management and outcomes of pregnant women with epilepsy. Method: The hospital database was analysed for 43 102 pregnant women who attended between 2002 and 2008. 141 women with diagnosed epilepsy were identified. Various aspects including demographics, neurological management and care in preconception and pregnancy were analysed. Results: Annual incidence was 20 per year (0.33%). Only 21(16%) received preconceptual advice. 78(55%) patients had a documented seizure type. These included tonic-clonic 54 (69%), myoclonic 7 (9%), partial 3 (4%) and absent 14 (10%). 40 (30%) out of 132 questioned had seizures within 1 year preconception. 22 (15%) had preconceptual folate. 20 (90%) were on 5 mg folate and remainder on 10 mg. Treatment strategy included 109 (77%) monotherapy, 13 (9%) polytherapy, 6 (4%) untreated and 13 (9%) stopped. 89 (63%) had vitamin K. 75 (83%) were commenced at 36 weeks. 2 (1%) patients had fetal anomalies – hydronephrosis and a cystic renal lesion. 42 (31%) needed induction of labour of which 5 (11%) were induced for poor seizure control. Complications included peripartum seizure 5 (3.54%), caesarean section (CS) 28 (20%), assisted delivery 15 (10%), fetal distress 12, malposition 10, obstructed labour 7 and post partum haemorrhage (PPH) 1. 98 (78%) patients received anti epileptic drugs in labour. Recommendations: (1) At preconception – Promote folate and optimum medications. (2) AEDs throughout pregnancy and the peripartum period are important. (3) Consider reduction of polytherapy. (4) ICPs help guide and improve healthcare.